Association between left ventricular ejection fraction and Kawasaki disease shock syndrome. (20th February 2019) - Qiu, Huixian; Li, Chen; He, Yuee; Weng, Fengfeng; Shi, Hongying; Pan, Lulu; Guo, Yuping; Zhang, Yuanhai; Wu, Rongzhou; Chu, Maoping
Abstract: Objective: This study was performed to explore the clinical features of Kawasaki disease shock syndrome and analyse the association between the left ventricular ejection fraction and Kawasaki disease shock syndrome. Methods: We retrospectively reviewed the medical records of all consecutive inpatients with Kawasaki disease at Wenzhou Medical University Second Affiliated Hospital and Yuying Children's Hospital in Wenzhou, China from January 2009 to December 2016. We compared the clinical characteristics, laboratory data, and left ventricular ejection fraction between patients with and without Kawasaki disease shock syndrome and analysed the effect of the left ventricular ejection fraction on Kawasaki disease shock syndrome under different clinical conditions of Kawasaki disease. Results: In total, 1147 patients were diagnosed with Kawasaki disease. Of these 1147 patients, 17 were diagnosed with Kawasaki disease shock syndrome; 68 patients admitted to the hospital at the same time, ±2 weeks, with Kawasaki disease but without Kawasaki disease shock syndrome served as the control group. Compared with the control group, the Kawasaki disease shock syndrome group had a significantly higher incidence of coronary artery lesions, cardiac troponin I concentration, N-terminal prohormone of brain natriuretic peptide concentration, neutrophil count and ratio, alanine aminotransferase concentration, aspartate aminotransferase concentration, and C-reactive protein concentration and a significantly lower platelet count, serum albumin concentration, and left ventricular ejection fraction. A low left ventricular ejection fraction was associated with Kawasaki disease shock syndrome under different conditions of Kawasaki disease. Conclusion: Among patients with Kawasaki disease, cardiac injury is more likely in those with Kawasaki disease shock syndrome than without, and a low left ventricular ejection fraction may be associated with the development of Kawasaki disease shock syndrome.